FRI0163 Efficacy of The Biosimilar BOW015, Compared To Originator Infliximab, Initiated at Moderate and Severe Disease Activity Thresholds in Rheumatoid Arthritis. (15th July 2016) - Taylor, P.; Wyand, M.; Knight, A.; Costantino, C.; Lassen, C.
Abstract : Background: In 2010 the British Society of Rheumatology guidelines 1 adjusted the recommended threshold for biologic therapy in rheumatoid arthritis (RA) to a DAS28 score of >3.2, from a DAS28 score of >5.1. However, adoption of this recommendation for the use of TNF-inhibitors such as infliximab in RA patients with moderate disease activity despite methotrexate may be limited, especially in regions that wish to minimise biologic usage due to cost. Objectives: To examine the effectiveness of Remicade (rIFX) in RA patient subgroups with severe or moderate disease activity, and to compare the efficacy of this treatment to BOW015, an infliximab biosimilar. Methods: Sub-groups of RA patients on a stable dose of methotrexate which included a EULAR diagnostic criteria ≥6 and a CRP≥10 mg/L were identified from within the cohort of a randomised double-blind, group comparison of BOW015 compared to rIFX (2:1) treated with 3 mg/kg IV at Week 0, 2, 6, 14, 22, 30, 38, and 46. Subject responses to treatment (ACR20, 50 and 70) were followed up until the end of the blinded phase (Week 16) and also following the switch to a BOW015 in an open-label phase (until Week 54). Severe and moderate patient sub-groups were determined by DAS28 (>5.1, ≤5.1 - >3.2) and CRP (≤10, >10 - ≤20, and >20mg/L) status at Week 0 pre-treatment. Analysis of the difference in the proportions of subjects achieving ACR20, 50 and 70 between subgroups and within treatments were performed by Fisher's exact test and 95% confidence intervals by exact method for the difference in proportions. Results: 189 subjects entered the study, 127 were dosed with BOW015 and 62 with rIFX. At the end of the double-blind period, patients were transitioned to open label BOW015 (104 continued BOW015 and 53 switched to BOW015). ACR20 responses by both high and low-activity DAS28 subgroups were comparable (Figure 1 ). There was no significant difference in proportions of ACR20 response to BOW015 or rIFX during the double-blind period and in the open-label period for those continuing on BOW015. Comparisons of ACR20 response by CRP sub-group were not significantly different during the double-blind or open-label period between CRP categories for each treatment or previous treatment. Conclusions: The proportion of ACR20 responders to BOW0I5 is comparable across subgroups of RA with severe or moderate disease activity, as assessed by DAS28 and CRP. The increased financial burden of widening access of biologics to patients with moderate disease activity could be offset by use of less expensive biosimilars. References: Deighton C, Hyrich K, Ding T et al. BSR and BHPR rheumatoid arthritis guidelines on eligibility criteria for the first biological therapy. Rheumatology. 2010;49:1197–9. Acknowledgement: This research was sponsored by EPIRUS Biopharmaceuticals Inc. Disclosure of Interest: P. Taylor Consultant for: Epirus Biopharmaceuticals Inc. and Merck, M. Wyand Shareholder of: Epirus Biopharmaceuticals Inc., Employee of: Epirus Biopharmaceuticals Inc., A. Knight Consultant for: Epirus Biopharmaceuticals Inc., C. Costantino Employee of: Epirus Biopharmaceuticals Inc., C. Lassen Shareholder of: Epirus Biopharmaceuticals Inc., Employee of: Epirus Biopharmaceuticals Inc.